แนวทางการพัฒนาช่องทางการขายตรงข้าวจากชาวนาสู่ผู้บริโภค จังหวัดศรีสะเกษ (กรณีศึกษาทุ่งกุลาร้องไห้ - ราเต ผศ.ดร.ลินดา (Research and Development Journal Sisaket Rajabhat University, 2020)
The purpose this research was to Study the status of development of direct sales for rice, problems and obstacles and to give gidelines for the development of direct sales for rice farmers to consumers in Sisaket provinces (A case study of Thung Kula Ronghai). The Qualitative research used in-depth interview with 45 persons consisted of Stakeholder of community enterprise of rice product group have succeeded. Synthesizing is the development of direct sales for rice farmers and focus group, with 15 persons, and then bringing the results got to check by the method of Quantitative research. From 258 samples by the use of Proportional Stratified Random Sampling and then suggesting the results of data synthesis, with average and standard deviation. The results found that, The development of direct sales for rice farmers to consumers namely SLOG Model coming from S: Social; namely building the society, L: Learn; namely learning, O: Organize; namely management and G: Group; namely integration. The results from focus group found that knowledgeable people agree with SLOG Modeland when it is brought to check for assuring the results with samples found that samples agree with the most of all strategies.